Pharmacological Management of Chronic Obstructive Lung Disease (COPD). Evidence from a Real-World Perspective - Part 2 - Kisialiou, Aliaksei; Prinzi, Giulia; Lamonaca, Palma; Cardaci, Vittorio; Tomino, Carlo; Fini, Massimo; Bonassi, Stefano; Russo, Patrizia (Current Medicinal Chemistry, 2019)
Background: We report a comprehensive overview of current COPD therapies from a real-world experience. Objective: Critically review the opportunities and the challenges occurring in the real-world treatment of COPD. Methods: This is a review that also report results from COPD patients treated with standardized therapy including pulmonary rehabilitation (Real World Data – RWD). Conclusion: Comprehensive assessment of COPD management requires strategies able to evaluate efficacy and usefulness in a real-world population, that take into account the interaction between experience and academic training, research, adherence to guidelines and judgments in order to plan the appropriate and optimum use of available strategies.
Keywords: Classical-therapy